Caracterização e atividade biológica de Polistes canadensis - Guimaraes, Tais Xavier (2012)
Wasp venom had proven to be a valued source of pharmacogically active compounds, capable of performing diverse functions. By acting on different biological systems, the characterization of such compounds exerts great interest in the prospection of new drugs. This work aimed to study the chemical extracts of Polistes canadensis and its potential antimicrobial tests ahead and toxic. For the research was carried out on the two collections in the Insituto de Planatas Medicinais (Manaquiri), AM, in epoch different. The crude venom was extracted methanol (MeOH) and water (H2O), fractioned by liquid chromatography classical (LCC), and 56 fractions were eluted, were investigated by high performance liquid chromatography (HPLC) and Mass Spectrometry (MS). The minimal inhibitory concentration (MIC) of crude venom of P. canadensis was determinated against Klebsiella pneumoniae, Flavobacterium columnae and Staphylococcus aureus. As the Minimum Bactericidal Concentration (CMB), the lowest value found was 125 g/mL. Keywords: wasp venom, Polistes canadensis, antimicrobial.